Numerical study of head-on droplet collisions at high Weber numbers. (26th January 2016) - Liu, M.; Bothe, D.
Abstract : Head-on collisions of binary water droplets at high Weber numbers are studied by means of direct numerical simulations (DNS). We modify the lamella stabilization method of Focke & Bothe ( J. Non-Newtonian Fluid Mech., vol. 166 (14), 2011, pp. 799–810), which avoids the artificial rupture of the thin lamella arising in high-energy collisions, and validate it in the regime of high Weber numbers. The simulations are conducted with and without initial disturbances and the results are compared with the experimental work of Pan et al.  ( Phys. Rev. E, vol. 80 (3), 2009, 036301). The influence of initial white noise disturbance on the collision dynamics is identified and good agreement between the simulation results and the experimental results is obtained when the initial noise disturbances are properly exerted. In order to include the stochastic nature of the disturbance, we conduct several simulations with white noise disturbance of same strength and average the spectrum diagram for the unstably developing rim of the collision complex. We show that the magnification of rim perturbation can be predicted by Plateau–Rayleigh theory over a long time span.